UMP students successfully achieved third place in the MAKUM 2023 Photography Competition - Nur Ainaa Adhreena, Muhamad Shukri (UMPSA, 2023)
SABAH, 1 Jun 2023 - Muhammad Amir Nuruddin Abdul Jalil, a student from the Faculty of Electrical and Electronics Engineering Technology (FTKEE), Universiti Malaysia Pahang (UMP), successfully secured third place in the overall Malaysian Universities Cultural Council (MAKUM) Sabah Culture Exploration Photography Competition held in Sabah recently.